Adherence to the planetary health diet is associated with slower cognitive decline: a prospective cohort analysis of Chinese older adults - Lulu Tang; Xiaoli Yu; Changcui Qiu; Yu Lu; Yunlan Wang; Fei Liu; Xiaoping Zhu (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background The EAT-Lancet commission has proposed a planetary health reference diet (PHD) aiming to improve human health and global environmental sustainability. Emerging evidence suggests that high-quality diet is a modified risk factor cognitive decline. However, population-based evidence in relation to the association between this diet and cognitive decline is scarce. Methods This prospective cohort study examined data from the China Health and Nutrition Survey (CHNS) during 1997–2011.We included 3404 adults aged 60 years and older with normal cognition at baseline. Dietary intake was assessed using 3-day 24 h dietary recalls combined with weighing methods and cognitive function was assessed using repeated measures of the Telephone Interview for Cognitive Status-modified (TICS-m). The Planetary Health Diet Index (PHDI) was based on 14 food groups and a total score from 0 to 140. Higher scores indicated greater adherence to the PHDI. We used linear mixed model with random intercepts and slope to evaluate the association between PHDI score and cognitive decline adjusting for demographic, health, and lifestyle confounders. Results During a median follow-up of 12 years, higher adherence to the PHDI was associated with a slower decline in memory and global cognition. Participants in the highest quintile of PHDI adherence had significantly slower memory decline (B = 0.025, 95%CI:0.000-0.049, P for trend = 0.019) and global cognitive decline (B = 0.020, 95%CI:0.004–0.037, P for trend = 0.029) compared to those in the lowest quintile. Stratified analyses revealed that physical activity modified these associations (P < 0.05). Among participants engaging in vigorous physical activity, those in the highest PHDI quintile exhibited an attenuated annual memory decline (B = 0.070, 95%CI:0.010–0.130, P for trend = 0.013) and global cognitive decline (B = 0.045, 95%CI:0.003–0.086, P for trend = 0.037) compared to those in the lowest quintile. Conclusion Higher adherence to the PHD was associated with slower cognitive decline in older Chinese adults. Physical activity, particularly vigorous physical activity, may enhance the cognitive benefits of this dietary pattern. These findings highlight the potential dual benefits of sustainable dietary patterns for both environmental and cognitive health.